Expressão de fatores ligados à apoptose : herpesvirus bovino tipo 5 - Antello, Talita Fontes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Belonging to the family Herpesviridae, subfamily Alphaherpesvirinae, bovine Herpesvirus type 5 ( BoHV-5) is the causative agent of bovine non-suppurative meningoencephalitis, which predominantly affects young cattle. In Brazil, cases of encephalitis caused by BoHV-5 are the second leading cause of deaths in the herd. Viral infection usually results in a change in the programmed cell death via mitochondrial, stimulating or inhibiting apoptosis related genes, promoting viral replication and dissemination process. The present study aimed to analyze the expression of apoptosis related genes (Apaf-1, TNFα-R1, FasL and cytochrome c) in infected or uninfected MDBK cells with BoHV-5. We observed an increase ( p < 0.05 ) in expression of the genes studied for the infected group compared with controls, in different times post-infection experimental. In the case of the Herpesviridae family, modulation of apoptosis appears to be a key step in its pathogenesis, despite the association of anti and pro-apoptotic activities with BoHV-5 is completely unknown. This study demonstrates the ability of BoHV-5 in modulating either activating or inhibiting the extrinsic pathway of apoptosis

Pertencente a família Herpesviridae, subfamília Alphaherpesvirinae, o Herpesvírus bovino tipo 5 (BoHV-5), é o agente causal da meningoencefalite bovina não supurativa, que atinge majoritariamente bovinos jovens. No Brasil, os casos de encefalite por BoHV-5 são a segunda maior causa de óbitos no rebanho. A infecção viral geralmente resulta em alteração no processo de morte celular programada, pela via mitocondrial, estimulando ou inibindo genes relacionados à apoptose, favorecendo a replicação e disseminação viral. O presente estudo teve como objetivo a análise da expressão de genes relacionados à apoptose (Apaf-1, α, FasL e citocromo c) em células MDBK infectadas ou não com o BoHV-5. Foi possível observar um aumento (p<0,05) na expressão dos genes estudados para o grupo infectado comparado ao controle, em diferentes momentos pós-infecção experimental. No caso da família Herpesviridae, a modulação da apoptose parecer ser uma etapa chave para sua patogênese, apesar da associação das atividades anti e pró-apoptóticas com o BoHV-5 ser completamente desconhecida. Este estudo demonstra a capacidade do BoHV-5 em modular, seja ativando ou inibindo, a via extrínseca da apoptose
Keywords: Microbiologia veterinaria; Virologia veterinaria; Apoptose; Virus do herpes em animais; Celulas - Cultura e meios de cultura; Veterinary microbiology